Essential oils from Elettaria cardamomum (L.) Maton grains and Cinnamomum verum J. Presl barks: Chemical examination and bioactivity studies. - Wael A. Al-Zereini; Ibrahim N. Al-Trawneh; Mahmoud A. Al-Qudah; Heba M. TumAllah; Hamas A. Al Rawashdeh; Zaed H. Abudayeh (GarVal Editorial Ltda., 2022)
Context: Elettaria cardamomum (L.) Maton grains and Cinnamomum verum J. Presl barks are immensely consumed by Jordanian population as food flavoring and remedies in treating different disorders without awareness of their effect or dose toxicity. Aims: To evaluate the antibacterial, antioxidant and cytotoxic effects of essential oils (EOs) hydro-distilled from E. cardamomum grains and C. verum barks. Methods: Hydro-distillation was carried out using Clevenger apparatus; the EOs were analyzed using GC/MS, and their constituents were quantified using GC/FID. The antibacterial activity was determined by agar diffusion test and micro-broth dilution assay, while the antioxidant activity was evaluated by DPPH and ABTS scavenging assays. The cytotoxic activity was evaluated against the MDA-MB-231 breast cancer cell line. Results: E. cardamomum EO was most effective against Bacillus subtilis with MIC 3.75 µL/mL and exhibited antioxidant activity in DPPH assay with IC50 0.057 ±0.013 µL/mL (0.076 ±0.017 µL EO/µg Trolox®) but was ineffective in the ABTS test up to 5 µL/mL; 86.22% of its EO constituent are oxygenated monoterpenes with α-terpinyl acetate as the major component. Whilst C. verum EO was active against both tested Gram-positive and negative bacterial strains with MIC 1.25-5.00 µL/mL but was devoid of significant antioxidant activity up to 5 µL/mL; phenylpropanoids constituted 69.48% of its EO with E-cinnamaldehyde as the major component. Both EOs showed cytotoxic activity against the breast cancer cell line withIC50 0.14-0.46 µL/mL. Conclusions: The current results unveil the potential application of C. verum and E. cardamomum in complementary and alternative medicine as biosafe remedies besides their usage as flavoring and seasoning sources.